PENGARUH PEMBERIAN EKSTRAK ETANOL KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) TERHADAP KADAR MDA (MALONDIALDEHYDE) LIVER PADA TIKUS MODEL MENOPAUSE - savitri, ananda savitri (E-Jurnal Medika Udayana, 2022)
Menopause characterized by stopped of ovaries producing estrogen, so the female reproductive system will gradually stop. There will be decrease the body's metabolic function and of various organs, on of that is liver. This is because, besides as  hormone, estrogen also works as an endogenous antioxidant for body. MDA is an organic compound as marker of oxidative stress in the body. In menopausal conditions, there will be increase oxidative stress, this because of an inparity in production of free radicals with antioxidants endogen. So that menopause tends to increase MDA levels. Increased levels of MDA in liver will cause problems, such as: non-alcoholic liver disease, liver fibrosis, and liver malignancy. The sample subjects divided into three groups, there are control sample (P0), the test group with ethanol extract of the peels from red dragon fruit dose 60 mg / 200grBB / day (P2), and the test group with ethanol extract of the peels from dragon fruit  dose 90 mg / 200grBB / day (P3). The average liver MDA value of P0  was 7,61-11,2, the highest average MDA level. The mean liver MDA value of P1 was 2,34-3,79 the lowest mean of serum MDA levels. The mean liver MDA levels in subjects of P2 was 2,64-3,97. Antioxidants  have similar structures with phytoestrogens chosen as endogenous estrogen substitutes. One of the anthocyanin-rich is peels of red dragon fruit, it hoped the extract can become an exogenous antioxidant in menopausal therapy.   Keywords : MDA, Red Dragon Fruit Peels, Antioxidant